DEVELOPING INNOVATIVE RECOMMENDATION AND PERSONALIZATION ENGINES TO IMPROVE USER EXPERIENCE ON THE TRADING PLATFORM - Tashmukhamedova Gulchekhra Takhirovna; Saidov Arslon Davron o’g’li; Davronov Murodjon Shuxrat O‘g‘li (Research Focus International Scientific Journal, 2022)
This article explores the development of innovative recommendation and personalization mechanisms to enhance the user experience in a shopping platform. The implementation of effective recommendation engines and personalization techniques in online shopping can significantly improve customer engagement, satisfaction, and conversion rates. The article investigates various algorithms and methods used to develop recommendation engines, including collaborative filtering, content-based filtering, and hybrid approaches. It also delves into personalization techniques such as user profiling, preference analysis, and contextual recommendations. Furthermore, the article discusses the integration of recommendation engines and personalization mechanisms into shopping platforms, considering scalability and real-time recommendations. Evaluation metrics and success indicators are proposed to measure the impact of these mechanisms on user experience and business outcomes. The article concludes by presenting case studies and practical approaches that highlight successful implementations of recommendation and personalization in shopping platforms.